The Level of Community Participation in Supporting Community-Based Tourism on Mount Merapi Slope - Muhamad Muhamad; Syamsul Maarif; Slamet Widiyanto (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2021)
This community service was carried out on the Mount Merapi slope, located around the 8-kilometer area, which falls in category III disaster-prone area. The main aim of this activity was to increase the community participation in developing their area through tourism. The method used here was Focused Group Discussion (FGD) that aimed at inviting and accommodating community participation, as well as a structured interview. The analysis employed 0-5 Likert scale containing score weight to identify the factors influencing participation forms and participation benefits. This research used the quantitative descriptive approach to describe the community level of participation. The result shows that the majority of residents (60%) participated in tourist village management, around 25% participated due to their awareness, around 12% participated without serious intention, and 3% did not participate. It can be concluded that they show high level of participation in supporting tourist village development in disaster-prone area.